The Effect of picture storybook based on scientific approach through ınquiry method toward student’s ınference skill - Atıkoh, Nur; Prasetyo, Zuhdan Kun (Journal of Turkish Science Education, 2018)
Many recent studies have reported that picture storybook plays a very important to make a meaningful learning. However, there is lack of the picture storybook that supports the learning process using a scientific approach. Thus, the student's scientific process skill will not develop optimally if the presentation of the material is less interesting and the students are not directly involved in the learning process. This study aimed to examine the difference of students’ inference skill after they were taught using picture storybook based on scientific approach through inquiry method and using textbook of curriculum 2013. The used research design was quasi-experiment with the model of pre-test and post-test control group design. The population of research used in this research was grade 5 students of the elementary school in Bantul, Yogyakarta. The sample of research consisted of 47 students. 23 students as experiment class using picture storybook based on scientific approach through inquiry method, whereas 24 students as control class using textbook of curriculum 2013. The result of research showed that there was a significant difference in learning student’s inference skill using picture storybook based on scientific approach through inquiry method and using textbook of curriculum 2013. It could be seen from the significance value (Sig.) lower than the significance level (α), (0,01 < 0,05). The implication of this research is the learning design will be more creative, innovative, and comprehensive.
Keywords: inference skill; inquiry method; picture storybook; scientific approach